1992
DOI: 10.1055/s-2007-1006690
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Growth-Plate Transplantation: A Comparative Study in the Rat

Abstract: The purpose of this study was to evaluate the influence of hormonal milieu on endochondral growth. This was achieved by transplanting hind limbs of juvenile rats to syngeneic adult rats. Because there is no potential for rejection, the limb can be transplanted between animals of different ages, to study the influence of hormonal maturity on stimulation and cessation of physeal growth and maturation. Tibial length and the histologic appearance of the physis were recorded. Whole vascularized hind-limb transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Chiu et al [12], in a similar study involving limb transplantation between animals of different ages, observed that the transplanted bone achieved only 70% of the normal growth in length. This finding was corroborated by Drzewiecki et al [11] who also found that after limb transplantation the transplanted bone could not achieve normal growth potential, but noted that the maximum growth (91% of normal) was observed in heterochronografts. However, in both of these studies the nerves of the transplanted limbs were not sutured, and the animals were non-weight bearing, so the failure to achieve full growth could be attributed to the effects of denervation and lack of external stress.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Chiu et al [12], in a similar study involving limb transplantation between animals of different ages, observed that the transplanted bone achieved only 70% of the normal growth in length. This finding was corroborated by Drzewiecki et al [11] who also found that after limb transplantation the transplanted bone could not achieve normal growth potential, but noted that the maximum growth (91% of normal) was observed in heterochronografts. However, in both of these studies the nerves of the transplanted limbs were not sutured, and the animals were non-weight bearing, so the failure to achieve full growth could be attributed to the effects of denervation and lack of external stress.…”
Section: Discussionsupporting
confidence: 65%
“…However, they yield conflicting results; some report that juvenile growth plates attain full growth potential in the adult body[1,10] while others report that juvenile growth plates attain only partial growth potential in the adult hormonal environment[11,12]. Vascularized growth plate transplants are now feasible alternatives for the management of growth plate damage by tumor, infection, trauma or congenital anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Organ development therefore requires a coordinated regulation of growth and is governed by regulatory mechanisms that remain essentially unknown. Data from previous studies suggest that the growth rates of transplanted organs are defined by the age of the donor rather than by the age of the recipient . This leads to the suggestion that termination of organ development is not under systemic control (e.g.…”
mentioning
confidence: 99%